قطع الكبد الجراحي للنقائل الورمية من سرطانات القولون و المستقيم (Latakia University Journal -Medical Sciences Series, 2018)
شملت الدراسة 11 مريضاً بنسبة 63.6% للإناث ومتوسط الأعمار 55.4 سنة. لقد توضع الورم البدئي في المستقيم في 36.4% و تم تشخيص وجود النقيلة او النقائل الكبدية بشكل متزامن مع تشخيص الورم  البدئي في 4  حالات و بنسبة 36.4% بينما تم حدوث النقائل الكبدية بشكل متأخر في 63.6% من الحالات. وجدت النقيلة الوحيدة عند 72.7% بينما شكلت النقائل المتعددة نسبة 27.3%. و كان قطر النقيلة اقل من 5 سم في 5 حالات و بنسبة 45.4% و كانت اكبر او يساوي 5 سم في 54.6% من الحالات. تم اجراء قطع كبد للنقيلة بشكل متزامن مع استئصال الورم البدئي الموجود في القولون في حالة واحدة فقط و كانت نقيلة وحيدة و بنسبة 9.1% من الحالات. شكل قطع الكبد لقطعة او قطعتين كبديتين الاجراء الجراحي الاكثر تواترا و بنسبة 45.4% من الحالات في حين تم اجراء قطع فص كبدي ايمن تام في حالة واحدة و كذلك قطع فص كبدي ايسر تام ايضا في حالة وحيدة. حدث تجمع صفراوي تالي للجراحة في حالة واحدة و لم تستدعي التداخل الجراحي. و حدث النزف الدموي بشكل فعال في حالة واحدة وحدث الناسور الصفراوي في حالتين و لم تحدث أية وفاة خلال الاشهر الثلاثة الاولى التالية للجراحة. معدل البقيا للسنة الاولى كانت بنسبة 100% اما البقيا لمدة بين 3 الى 5 سنوات فكانت 45% و في حالة واحدة تجاوزت البقيا 5 سنوات Introduction: Liver surgery is a relatively recent and relatively major complex surgery, due to the anatomical and histological specialty of the liver Objective of the research: To evaluate the results of the cases of liver metastases from colorectal carcinoma from November 2010 until the end of April 2017.The study included 11 patients with 63,4% of females and average age of 55,4 years. The primary tumor was located in the rectum at 36.4%. in 4 cases (36.4%) was the livermetastases as a synchron with the main tumor while the metachron metastases was in 63.6% of cases. The single metastases was found at 72.7% while the multiple metastases accounted for 27.3%. The transfusion diameter was less than 5 cm in 5 cases and 45.4% and it was larger or equal to 5 cm in 54.6% of all the cases. The liver resection for Hepatocellular lesions were performed concurrently with primary tumor resection in the colon in only one case and the metastases was a single and 9.1% of the cases. The most common surgical procedure was segment resection in 45.4% of all the cases. The left or right hemi hepatectomy was in two cases, 8.7% None of the patients had any complications which requiring a reoperation. Bleeding occurred in one case such as the Bilioma in one case and Biliary fistula occurred in two cases. The survival time for the first year was 100% and 45% for (3-5) years and in one case till now mor than 5 years.